The Importance of Bank Transformation and Digitization - Toshtemirovich, Mamadiyarov Zokir (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In this article, the global trends in the transformation and digitalization of banks and the work being done in this regard in the banking system of Uzbekistan are widely covered. In particular, the emergence of digital banks, foreign experience and their importance were analyzed based on statistical data. As a result of this research, it is necessary to develop conclusions and scientific proposals regarding the transformation and digitization of banks.